PEMANFAATAN MODEL BAHAN AJAR PADA MATERI MENULIS CERPEN - Ridha Shafa Aulia; Wahyu Sukartiningsih; Titik Indarti (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Short story writing skills are considered complex skills and difficult to master. The obstacles when learning to write short stories are in students who tend to be lazy to read, while external factors lie in the availability of teaching materials, media, and strategies used by the teacher. The research objective was to determine the model of teaching materials in short story writing material. This type of research uses qualitative research with literature review methods. The library selection technique is based on the keywords of the teaching material model in short story writing material. The literature comes from accredited national journals on Google Scholar with a publication limit of the last 10 years. The literature study technique uses a synthetic matrix based on reference sources, sample types, methods, interventions, and findings. The conclusion is that the teaching material model in writing short story materials can be done using the storyboard learning method, experience, paraphrasing, short stories gram, audiovisual media, documentary films, and adobe flash.